'My beloved leader': Tracing the leader-centred perspective in the Turkish Grand National Assembly, 1961–2002. (2nd January 2021) - Bahadır Türk, H.; Emrah Beriş, Hamit; Önder, Tuncay
ABSTRACT: Political leaders are the key actors in Turkish politics. Historically, they have been considered much more crucial than political institutions. They are the objects of love, hate, hope and fear in Turkish political life. Drawing upon semi-structured interviews with 37 former Members of Parliament (MPs), this study attempts to make sense of the leader-centred perspective in the Turkish Grand National Assembly (TGNA). To achieve this goal, the study demonstrates the reflections of this perspective in the narratives of the former MPs during the period between 1961 and 2002.